New concepts of the power received by ideal energy storage elements: the instantaneous complex power approach - Milanez, Dalgerti Lelis Autor [UNESP]; Cameron, G.; Hassoun, M.; Jerdee, A.; Melvin, C. (Institute of Electrical and Electronics Engineers (IEEE), 1996)
This paper presents some definitions and concepts of the Instantaneous Complex Power Theory [1] which is a new approach for the Akagi's Instantaneous Reactive Power Theory [2].The powers received by an ideal inductor are interpreted and the knowledge of the actual nature of these powers may lead to changes of the conventional electrical power concepts.